The political economy of uneven and combined development : the case of North East England - Hudson, Ray, 1948- (Routledge advances in regional economics, science and policy., 2025)
"The focus of this book is the processes through which industries and regions grow and decline in capitalist economies via an investigation of the trajectory of change in the North East of England. How and why did its economy grow from the sixteenth century to be a 'Workshop of the World' by the outbreak of the First World War, only to collapse a decade later? How and why did the region then become a laboratory for experiments in state policies to reverse economic decline, policies that have largely failed? How did the region become transformed from one with indigenous innovative firms, to one of foreign branch plants focused on routine component production and assembly, to a deindustrialised region which became the destination for call centres and Amazon distribution centres? What were the economic, labour market and social consequences of these changes? The account of regional change is framed in terms of uneven and combined development, temporally, spatially and between and within the broad classes of Capital and Labour. The core message of the book is that the growth and decline of the region and of the changing map of regional development, is most appropriately understood within a conceptual framework of uneven and combined development grounded in Marxian political economy. The book will be of interest to academic researchers and students of political economy, regional development, geography, sociology, planning and policy studies as well as policy makers in central, regional and local government"--